Abundance : on the experience of living in a world of information plenty - Boczkowski, Pablo J. (New York, NY : Oxford University Press, 2021)
"The book examines the experience of living in a society that has more information available to the public than ever before. It focuses on the interpretations, emotions, and practices of dealing with this abundance in everyday life. Drawing upon extensive fieldwork and survey research conducted in Argentina, the book inquiries into the role of cultural and structural factors that mediate between the availability of information and the actual consequences for individuals, media, politics, and society. Providing the first book-length account of the topic in the Global South, it concludes that the experience of information abundance is tied to an overall unsettling of society, a reconstitution of how we understand and perform our relationships with others, and a twin depreciation of facts and appreciation of fictions"--
Abundance -- Screens -- Platforms -- News -- Entertainment -- Scarcity.
Includes bibliographical references (pages 195-210) and index.
Keywords: Information society; Information technology -- Social aspects -- Argentina; Mass media -- Social aspects -- Argentina; Information behavior -- Argentina; Media literacy -- Argentina